Pleomorphic/solid lobular carcinoma of male breast with PALB2 germline mutation: case report and literature review - Rogges, Evelina; Corati, Tiberio; Amato, Michela; Campagna, Domenico; Farro, Juliette; De Toffol, simona; Fortunato, Lucio; Costarelli, Leopoldo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Male breast cancer (MBC) accounts for approximately 1% of all breast cancers and among these infiltrating lobular carcinomas (ILC) represents only 1-2% of all MBC cases. Pleomorphic invasive lobular carcinoma (PILC) is an aggressive variant of ILC with only eight cases reported until now in males. Up to 10% of MBC cases have a germline pathogenic variant in a predisposing gene such as BRCA1 and BRCA2 genes. Mutations in PALB2 (partner and localizer of BRCA2) have been reported in men with breast cancer, with a frequency that ranges from 0.8 to 6.4%, but it has never been reported in male ILC. Here, we report a rare and interesting case of an invasive pleomorphic/solid lobular carcinoma, which carries a pathogenic variant in PALB2 gene, and a family history of breast cancer without other well defined risk factors for developing this type of neoplasia. In addition, we review the current literature.